Exploring the relationship between metacognitive awareness and Chinese EFL learners’ listening skills - Fu, Ying; Wang, Min; Min, Shangchao; Zhou, Songbo; Pan, Xunyi (Frontiers in Psychology, 2023)
Listening causes great difficulties for EFL learners and little is known concerning the contribution of EFL learners’ metacognitive awareness to their listening performance and to their mastery of listening subskill. In the present study, the Metacognitive Awareness Listening Questionnaire (MALQ) and an in-house listening test were used to collect data from 567 Chinese EFL college students. The G-DINA package in R was adopted to identify students’ mastery patterns of listening subskills. The correlations of test takers’ MALQ results and their listening scores and listening subskills mastery probability were analyzed, respectively, to investigate how test participants’ metacognitive awareness relates to their language proficiency and listening subskills. According to the study, learners’ metacognitive awareness has a significant positive relationship with their listening performance at overall and subskills levels. The findings of the study provide additional evidence for using the MALQ as an instrument to interpret learners’ metacognitive awareness of listening strategies. It is thus recommended that theorists and language teachers involve metacognitive awareness of strategies in listening instructions.